RUPTURE OF A PANCREATIC PSEUDOANEURYSM AS A CONSEQUENCE OF CHRONIC PANCREATITIS: CASE REPORT OF A SURGICAL EMERGENCY - Perišić, Zlatko; Brkić, Dušan; Micić, Dušan; Doklestić Vasiljev, Krstina; Ćeranić, Miljan; Raspopović, Miloš; Vasin, Dragan; Hadžibegović, Adi; Gregorić, Pavle (Sanamed, 2024)
Introduction: Pseudoaneurysms of the pancreaticoduodenal arcade are rare, accounting for approximately 2% of all visceral artery aneurysms. They typically arise as complications of chronic pancreatitis, peptic ulcer disease, trauma, pancreatic and biliary surgery, or pancreas transplantation. Diagnosis often occurs only after rupture, leading to life-threatening internal bleeding. Bleeding may occur within a pseudocyst, with blood passing through the Vater's papilla into the digestive tract, or may result in the formation of a retroperitoneal hematoma that can rupture into the abdominal cavity, causing hemoperitoneum. The cell-saver is a tool that can be utilized for intraoperative blood cell salvage and autologous transfusions.Case Report: Our patient, a 54-year-old male, an untreated alcoholic with no prior medical history or documented treatment, presented to the Clinic for Emergency Surgery at the University Clinical Center of Serbia with a sudden onset of upper abdominal pain. A quick ultrasound of the abdomen was performed, followed by an urgent CT scan of the chest and abdomen, revealing a hematoma extending from the right retroperitoneum and mesentery of the intestine, measuring 150x109x180mm in diameter, with signs of active bleeding in the region beneath the pancreas, indicative of hemoperitoneum. Due to hemodynamic instability, accompanied by a drop in arterial blood pressure and hemoglobin levels, an urgent laparotomy was performed. Active bleeding was identified from a ruptured pseudoaneurysm originating from the pancreaticoduodenal arcade. Hemostasis was achieved followed by tamponade, and the tampons were removed 30 hours post-surgery. The patient remained hemodynamically stable thereafter, recovered well from the surgery, and was discharged home in good general condition.Intraoperatively, we utilized the Cell-saver to collect the patient's blood and subsequently administered autologous transfusion.Conclusion: In patients with chronic pancreatitis presenting with sudden abdominal pain and hemodynamic instability accompanied by a drop in arterial pressure, hemoglobin, and hematocrit levels, the possibility of a ruptured pseudoaneurysm in the pancreatic or peripancreatic region should be considered. Timely diagnosis and prompt surgical intervention are crucial for a successful outcome. Effective collaboration among radiologists, anesthesiologists, and surgeons is essential. The utilization of the Cell-saver system significantly aids in maintaining cardiac output and hemodynamic stability in these patients.
Keywords: pseudoaneurysm; rupture; chronic pancreatitis; emergency surgery